2021
DOI: 10.1093/rheumatology/keab151
|View full text |Cite
|
Sign up to set email alerts
|

Should we use glucocorticoids in early rheumatoid arthritis? Results at 5 years from the early RA UCLouvain Brussels cohort

Abstract: Objectives To evaluate the proportion of patients with ERA who have initiated or not GC, to analyse the baseline characteristics, and to assess the clinical benefit and side effects of GC during 5 years of follow-up. Methods We included patients with ERA from the UCLouvain Brussels cohort who met the ACR/EULAR 2010 classification criteria and were naïve to cDMARDs. We retrospectively collected patient characteristics prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…RMD Open RMD Open RMD Open recommending as first treatment strategy the initiation of disease-modifying antirheumatic drug (DMARD) such as methotrexate (MTX) with a short-term glucocorticoid (GC) course, 2 it is debated if this intensive approach is also necessary in patients lacking classical markers of poor prognosis. 3 In the Care in early RA (CareRA) trial, we demonstrated that also in patients without erosions, seronegative or with low disease activity, the speed of response was more rapid when treated with MTX plus a step-down-bridge GC scheme compared with MTX therapy without GC, while long-term treat-to-target results were comparable. [4][5][6] However, the potential advantage of intensive therapy on patient important outcomes such as pain and the concomitant use of non-steroidal antiinflammatory drugs (NSAIDs) and analgesics deserves more detailed study in relation to the clinical response to a treat-to-target approach, taking into account the cumulative need but also the evolution over time.…”
Section: Key Messagesmentioning
confidence: 94%
“…RMD Open RMD Open RMD Open recommending as first treatment strategy the initiation of disease-modifying antirheumatic drug (DMARD) such as methotrexate (MTX) with a short-term glucocorticoid (GC) course, 2 it is debated if this intensive approach is also necessary in patients lacking classical markers of poor prognosis. 3 In the Care in early RA (CareRA) trial, we demonstrated that also in patients without erosions, seronegative or with low disease activity, the speed of response was more rapid when treated with MTX plus a step-down-bridge GC scheme compared with MTX therapy without GC, while long-term treat-to-target results were comparable. [4][5][6] However, the potential advantage of intensive therapy on patient important outcomes such as pain and the concomitant use of non-steroidal antiinflammatory drugs (NSAIDs) and analgesics deserves more detailed study in relation to the clinical response to a treat-to-target approach, taking into account the cumulative need but also the evolution over time.…”
Section: Key Messagesmentioning
confidence: 94%
“…The infection rate was available for patients in 39 studies with 48 cohorts who were administered TNF-α inhibitors; however, only 2 studies reported the infection rate for all 5 types of TNF-α inhibitor drugs, 17,65 and most of the studies reported information for a couple of TNF-α inhibitor drugs.…”
Section: Tnf-α Inhibitorsmentioning
confidence: 99%